2021
DOI: 10.1177/11782218211039781
|View full text |Cite
|
Sign up to set email alerts
|

Barriers for Implementing the Hub and Spoke Model to Expand Medication for Opioid Use Disorder: A Case Study of Montana

Abstract: Purpose: Access to medication for opioid use disorder (MOUD) varies across the rural-urban continuum. The Hub & Spoke Model (H&S) emerged to address these gaps in service whereby hubs with staff expertise in MOUD support delivery of specialized care to a network of spoke locations, often located in rural communities with workforce shortages. This paper presents a case study of efforts to implement the hub and spoke model in a frontier and rural (FAR) state: Montana. Methods: The primary data are struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Such concerns echo financial, infrastructural, and geographic issues documented in the evolving literature on such programs. 42,43 Similarly, there have been substantial efforts to encourage linkage to MOUD for individuals being treated in emergency departments, with several states seeking to support such initiatives. 44,45 The panelists also raised questions about the feasibility of such approaches because of coordination and infrastructure complexities.…”
Section: Discussionmentioning
confidence: 99%
“…Such concerns echo financial, infrastructural, and geographic issues documented in the evolving literature on such programs. 42,43 Similarly, there have been substantial efforts to encourage linkage to MOUD for individuals being treated in emergency departments, with several states seeking to support such initiatives. 44,45 The panelists also raised questions about the feasibility of such approaches because of coordination and infrastructure complexities.…”
Section: Discussionmentioning
confidence: 99%
“…First responders in this study respond to these shortcomings by describing a lack of access to treatment and harm reduction services throughout Montana. Structural barriers constrain Montana’s ability to expand medication for opioid use disorder (see [ 34 ]), prompting calls for a more robust harm reduction strategy that compensates for the state’s insufficient treatment capacity [ 12 ]. One method that could reduce these structural barriers and improve layperson access to naloxone is the implementation of a mail-order naloxone program [ 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…National data from 2018 showed that too few (only 42%) substance use treatment providers offered medication for opioid use disorder (US Substance Abuse and Mental Health Services Administration, 2019), and many treatment options were concentrated in urban areas, which resulted in long wait times for admission and an increased risk of overdose for rural patients [ 2 , 34 , 57 , 64 ]. Previous studies suggest that a stronger connection to treatment and recovery services can bolster harm reduction efforts [ 71 , 76 , 37 ]; however, first responders located in the most remote and developed areas of Montana reported serving residents across vast geographic distances and expressed frustration with the lack of addiction treatment resources and lengthy waitlists that limit access to treatment for Montanans (also see [ 13 , 30 , 60 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations